Evaluating the Influence of Written Feedback in Elementary Mathematics - Miedzo Mutendi; Chipo Makamure (Current Research in Language, Literature and Education Vol. 3, 2022)
The purpose of this study was to explore the quality of written feedback that is suitable and understandable by primary school learners in mathematics. It is understood in literature that written feedback improves progress in learning elementary mathematics and that written feedback is an instructional strategy that accelerates the rate and amount of learning to improve learners’ achievement in mathematics. Additionally, written feedback is known to bridge the gap between the learner’s current understanding of a concept and the expected performance on the same concept. However, although written feedback is believed to be integral in learning primary school mathematics, there is less agreement on whether this is workable in the real world of the classroom, because of various challenges faced by both teachers and learners in terms of how they understand this kind of feedback. There is limited work in literature on how pupils respond to or use written feedback from their teachers to improve their performance. A questionnaire was administered to a group of Year 5 students at a school in England to solicit the pupils’ understanding of the usefulness of written feedback and the challenges that were likely to be faced in interpreting and implementing the feedback. In order to measure the impact of written feedback on learners’ performance, the learners wrote a pre-test, and their recommendations from the questionnaire were incorporated in the feedback. A second similar test was given two days later. The two sets of marks were then compared. It was found that learners find it difficult to understand written feedback at times, mainly because of unfamiliar vocabulary used in the feedback and when they do understand the language, they often find it unhelpful in achieving their learning goals. Some do not even read the written feedback. Teachers are recommended to simplify and add more detail to feedback, making it as informative as possible about what was done well and suggest improvements that could be made.